Economic Growth and Poverty of North Sumatera Province (Comparative Study Before and During the Covid-19 Pandemic) - Fitrawaty, Fitrawaty; Sinaga , Rosenta Febri Mutiara; Ananta, Dimas (Information Technology and Science (ITScience), 2024)
Economic growth and poverty levels are crucial indicators for assessing a country's development progress. When the coronavirus disease (COVID-19) pandemic hit Indonesia, both economic growth and poverty rates increased significantly. The widespread impact of the novel coronavirus has affected all aspects of life, particularly the economic sector. The increasing prevalence of the COVID-19 pandemic has directly contributed to rising poverty levels in various regions of Indonesia, including North Sumatra.This study utilizes data from the North Sumatra Central Statistics Agency before the COVID-19 pandemic (2015-2019) and during the pandemic (2020-2022). To evaluate the changes that occurred, the